I KNOW AND I LEARN! PRE-SERVICE TEACHERS REFLECT ON KWL IN TAIWAN - Muhammad Yunus; Muhammad Galuh Elga Romadhon (Indonesian EFL Journal, 2025)
Effective reading strategies for pre-service teachers are of critical importance in this day and age, amidst the changes taking place in English as a Foreign Language (EFL) classes. This study highlights the KWL (Know, Want to Know, Learned) strategy as a powerful approach to boost comprehension skills of prospective teachers. This qualitative case study conducted at National Ping Tung University (NPTU) in Taiwan draws from semi-structured interview data with master’s students who encountered KWL in their reading courses. Thematic analysis was employed not only to evaluate the effectiveness of KWL in the case but also to explore reading instruction in its more general aspects. The study's findings suggest KWL promotes enhanced engagement, reflective thought, and the integration of previous knowledge with new information. Still, participants noted some difficulties—particularly around setting clearly defined learning objectives and synthesizing essential information. Within these constraints, KWL proves to be a useful metacognitive framework in teacher education. The research argued for the application of structured approaches such as KWL to develop sophisticated reading strategies and to stimulate active learning. Subsequent research could explore the use of digital tools to broaden the application of KWL in diverse cultural and linguistic classroom settings.